Բանակցություններում միջնորդական առաքելությունների հիմնական խնդիրները և առանձնահատկությունները - Չալըմյան Նուբար (YSU Journal of International Affairs, 2017)
Mediation missions play an important role in international relations in regulation and resolution of conflicts. The general framework of the incurred responsibilities and key challenges are discussed in the article according to the adopted international standards and principles by the example of Minsk group cochairmen around Artsakh conflict regulation as efforts, made by mediation countries.